2016
DOI: 10.1007/978-3-319-44564-9_16
|View full text |Cite
|
Sign up to set email alerts
|

SS4MCT: A Statistical Stemmer for Morphologically Complex Texts

Abstract: There have been multiple attempts to resolve various inflection matching problems in information retrieval. Stemming is a common approach to this end. Among many techniques for stemming, statistical stemming has been shown to be effective in a number of languages, particularly highly inflected languages. In this paper we propose a method for finding affixes in different positions of a word. Common statistical techniques heavily rely on string similarity in terms of prefix and suffix matching. Since infixes are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Pande et al [62] also used an N-gram technique to develop a stemmer and frequency of the N-gram to determine the stem's possibility. Dadashkarimi et al [63] proposed a statistical stemmer to extract the root from the inflectional and derivational forms of the word. The method learns the linguistic pattern from the huge collection of web pages using Minimum Edit Distance (MED) algorithms and Parts of Speech (POS) tagger.…”
Section: B Statistical-based Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Pande et al [62] also used an N-gram technique to develop a stemmer and frequency of the N-gram to determine the stem's possibility. Dadashkarimi et al [63] proposed a statistical stemmer to extract the root from the inflectional and derivational forms of the word. The method learns the linguistic pattern from the huge collection of web pages using Minimum Edit Distance (MED) algorithms and Parts of Speech (POS) tagger.…”
Section: B Statistical-based Approachesmentioning
confidence: 99%
“…Ferilli et al [65] tested the stemmer on English, Italian, French, and Latin text. Statistical stemmers, evaluated in the context of IR systems such as Dadashkarimi et al [63] stemmer are shown in Table 15. Statistical stemmer's performance may vary from language to language as mentioned in Table 15, for example, a stemmer has achieved 92.63% accuracy for the Italian language whereas it achieved 89.54 for the French language.…”
Section: Performance Comparison and Critical Analysismentioning
confidence: 99%